Hip fracture, mortality risk, and cause of death over two decades. Issue 10 (October 2016) - Friesendorff, M.; McGuigan, F.; Wizert, A.; Rogmark, C.; Holmberg, A.; Woolf, A.; Akesson, K.
Abstract Summary Men and women with hip fracture have higher short-term mortality. This study investigated mortality risk over two decades post-fracture; excess mortality remained high in women up to 10 years and in men up to 20 years. Cardiovascular disease (CVD) and pneumonia were leading causes of death with a long-term doubling of risk. Introduction Hip fractures are associated with increased mortality, particularly short term. In this study with a two-decade follow-up, we examined mortality and cause of death compared to the background population. Methods We followed 1013 hip fracture patients and 2026 matched community controls for 22 years. Mortality, excess mortality, and cause of death were analyzed and stratified for age and sex. Hazard ratio (HR) was estimated by Cox regression. A competing risk model was fitted to estimate HR for common causes of death (CVD, cancer, pneumonia) in the short and long term (>1 year). Results For both sexes and at all ages, mortality was higher in hip fracture patients across the observation period with men losing most life years (p < 0.001). Mortality risk was higher for up to 15 years (women (risk ratio (RR) 1.9 [95 % confidence interval (CI) 1.7–2.1]); men (RR 2.8 [2.2–3.5])) and until end of follow-up ((RR 1.8 [1.6–2.0]); (RR 2.7 [2.1–3.3])). Excess mortality by time intervals, censored for the first year, was evident in women (<80 years, up to 10 years; >80 years, for 5 years) and in men <80 years throughout. CVD and pneumonia were predominant causes of death in men and women with an associated higher risk in all age groups. Pneumonia caused excess mortality in men over the entire observation period. Conclusion In a remaining lifetime perspective, all-cause and excess mortality after hip fracture was higher even over two decades of follow-up. CVD and pneumonia reduce life expectancy for the remaining lifetime and highlights the need to further improve post-fracture management.